Eficácia do treinamento de força sobre parâmetros cardiovasculares e antropométricos em adultos sedentários - Cabral, Carlos Ernani de Araujo Tinoco (2012)
This study aimed to determine the influence of strength training (ST), in three weekly sessions over ten weeks, on cardiovascular parameters and anthropometric measurements. It is a before and after intervention trial, with a sample composed of 30 individuals. Participants were adults aged between 18 and 40 years, from both sexes and sedentary for at least three months previously. Tests were computed ergospirometry, CRP, PWV and body composition (dependent variables) before and after the experiment. Independent variables, age and sex, were considered in order to determine their influence on the dependent variablesevaluatedend. By comparing the initial cardiovascular parameters with those obtained after intervention in patients undergoing the ST proposed (a Student s t-test was conducted within each group for samples matched to parameters with normal distribution, while the Wilcoxin was applied for those without), there was no significant difference in PWV(p =0469) or PCR(p =0.247), but there was an increase in anaerobic threshold(AT) (p=0.004) and Maximal Oxygen Uptake(VO2max) (p =0.052). In regard to anthropometric measures, individuals significantly reduced their body fat percentage (p<0.001) and fat mass (p<0,001), as well as increasing lean mass (p<0.001). However, no changes were recorded in the waist-to-hip ratio (WHR) (p= 0.777), body mass (p=0.226) or body mass index (BMI) (p =0.212). Findings of this study lead us to believe that the proposed ST, and did not increase the VOP or PCR improves cardiorespiratory capacity and body composition. Devotees of this training can therefore safely enjoy all its benefits without risk to the cardiovascular system